The influence of leadership and work motivation on employee performance of Perumda Tirta Benteng Tangerang City - Restika Ayu Purnamasari; Herayati Herayati; Martinus wahyu Purnomo (International Journal of Applied Finance and Business Studies, 2023)
Based on the results of the author's temporary observations, there are problems in terms of leadership and motivation. In terms of leadership, for example, leaders are often indecisive and do not exercise adequate oversight. This is very important to note because it can affect the performance of PERUMDA Tirta Benteng Tangerang City employees. The purpose of the authors to conduct this research is to find out and analyze the influence of leadership and work motivation both partially and simultaneously on the performance of PERUMDA Tirta Benteng Tangerang City employees. Data collection techniques using observation, interviews and distributing questionnaires to 39 respondents. The data analysis used was multiple linear regression test, F test and T test. The results obtained found that there was a positive influence on the leadership variable on employee performance based on T count greater than T table (2.486 > 2.02809). The same results indicated a positive and significant influence of work motivation variables on employee performance. Based on the results, T count is greater than T table (6,520 > 2.02809). As well as the simultaneous test results show that the variables of leadership and work motivation together have a positive and significant effect on employee performance variables at PERUMDA Tirta Benteng Tangerang City. With a calculated F value of 25.210 > F table of 3.25945.